A D-peptide ligand of neuropeptide Y receptor Y1 serves as nanocarrier traversing of the blood brain barrier and targets glioma. (June 2022) - Li, Yanying; Pan, Yuanbo; Wang, Yinjie; Jiang, Zhenqi; Akakuru, Ozioma U.; Li, Mingli; Zhang, Xianyun; Yuan, Bo; Xing, Jie; Luo, Lijia; Larhammar, Dan; Wu, Aiguo; et al.
Abstract: Diseases of the central nervous system (CNS) are challenging for drug treatment because the blood-brain barrier (BBB) restricts entry of drugs into the brain tissue. Therefore, strategies for drug transport across the BBB are an important component in development of CNS drug therapies. Here, a D -amino acid ligand of the neuropeptide Y (NPY) receptor Y1 is described, D [Asn 28, Pro 30, Trp 32 ]- D NPY (25−36) (termed D APT), with 2.5 times higher number of hydrogen bonds interacting with the receptor, based on docking into a structural model, than the corresponding peptide with standard L -amino acids ( L APT). Using in vitro BBB models, in vivo healthy mice with intact BBB, and U87-MG orthotopic tumor-bearing mice, we demonstrate that D APT exhibits significantly higher ability than L APT to serve as nanocarrier across the BBB and specifically targets gliomas. Using D APT nanomicelles loaded with IRDye780, it was possible to achieve excellent photothermal therapeutic and photoacoustic cancer imaging. Thus, this study demonstrates the importance of ligand stability and affinity in Y1 receptor-mediated transcytosis and paves the way for versatile brain tumor imaging and therapy using nanomicelles. Graphical Abstract: A D -peptide ligand of neuropeptide Y receptor Y1 serves as nanocarrier traversing of the blood brain barrier and targets glioma. Due to the higher stability and affinity of D -peptide ligand, the IRDye loaded nanocarriers could achieve excellent photothermal therapeutic and photoacoustic glioma imaging in vivo . ga1 Highlights: A novel D -peptide ligand of the neuropeptide Y receptor Y1 was firstly designed with higher enzyme stability, and prolonged the systemic circulation times of nanocarriers in vivo . The designed D -peptide ligand exhibited significantly higher affinity than L -peptide ligand to serve as nanocarrier across the blood brain barrier and specifically targeted glioma for its photothermal therapy and photoacoustic imaging.